DEVELOPMENT OF TECHNOLOGY FOR REDUCING THE TECHNOGENIC IMPACT OF SUGAR FACTORIES ON THE ENVIRONMENT OF LOCALITIES - Polivanova, Tatyana; Semicheva, Natalya; Ryabtseva, Svetlana (Journal of Applied Engineering Science, 2020)
This article describes technologies for reducing the technogenic impact of sugar factories on the environment of localities.
Keywords: agribusiness, sugar industry, ecology, ecologization, environmental protection measures